Complete genome of Staphylococcus aureus Tager 104 provides evidence of its relation to modern systemic hospital-acquired strains. (December 2016) - Davis, Richard; Brannen, Andrew; Hossain, Mohammad; Monsma, Scott; Bock, Paul; Nahrendorf, Matthias; Mead, David; Lodes, Michael; Liles, Mark; Panizzi, Peter
Abstract Background Staphylococcus aureus (S. aureus ) infections range in severity due to expression of certain virulence factors encoded on mobile genetic elements (MGE). As such, characterization of these MGE, as well as single nucleotide polymorphisms, is of high clinical and microbiological importance. To understand the evolution of these dangerous pathogens, it is paramount to define reference strains that may predate MGE acquisition. One such candidate isS. aureus Tager 104, a previously uncharacterized strain isolated from a patient with impetigo in 1947. Results We show here thatS. aureus Tager 104 can survive in the bloodstream and infect naïve organs. We also demonstrate a procedure to construct and validate the assembly ofS. aureus genomes, using Tager 104 as a proof-of-concept. In so doing, we bridged confounding gap regions that limited our initial attempts to close this 2.82 Mb genome, through integration of data from Illumina Nextera paired-end, PacBio RS, and Lucigen NxSeq mate-pair libraries. Furthermore, we provide independent confirmation of our segmental arrangement of the Tager 104 genome by the sole use of Lucigen NxSeq libraries filled by paired-end MiSeq reads and alignment with SPAdes software. Genomic analysis of Tager 104 revealed limited MGE, and a νSaβ island configuration that is reminiscent of other hospital acquiredS. aureus genomes. Conclusions Tager 104 represents an early-branching ancestor of certain hospital-acquired strains. Combined with its earlier isolation date and limited content of MGE, Tager 104 can serve as a viable reference for future comparative genome studies.